GAMBARAN PENGETAHUAN IBU TENTANG KONTRASEPSI TUBEKTOMI DI KLINIK HARAPAN IBU TAHUN 2015 - TISNILAWATI . (JURNAL ILMIAH KOHESI, 2018)
Indonesia's population is a population problem in Indonesia. Total populationIndonesia 782,682 who became KB participants. According to the 2013 BKKBN data (7.64%), 98,594 Implant participants(12.60%), 358,470 injection participants (45.80%), 203,878 Pil participants (26.05%), 13,623 MOW participants (1.74%),2,589 MOP participants (0.33%) and condom participants 45,753 (5.85%). The purpose of the research is to find outdefinition characteristics, advantages, weaknesses, indications, and contraindications in the Maternity Hope Clinic of the Year2015The study was descriptive to determine the description of maternal knowledge about contraceptiontubectomy with the population are all mothers who come to visit the Maternal Hope Clinic of the Year2015 from July 3 to July 5, as many as 30 respondents. Sampling techniques in researchthis is an incidental 30 respondents using a questionnaire. Analysis is discussed in accordance with the theoryand existing libraries.From the results of the researchers who used 30 respondents the majority of knowledge was not as good as many15 respondents (50%), and a well-informed minority of 13 respondents (43.3%). Based on age,the majority of respondents with enough knowledge were 27 respondents (90%) in the age group 20-35 years.And the minority is less knowledgeable as much as 1 respondent (3.3%) in the age group <20Year. Based on education, the majority are knowledgeable enough as many as 15 respondents (50%) athigh school education groups and less knowledgeable minorities as much as 1 respondent (3.3%) in the groupelementary education. Based on the source of information, the majority of knowledgeable as many as 20 respondents(66.6%) and a minority of poor knowledge about 18 respondents (6.6%).Based on the results of the study it can be concluded that the mothers who visited the Maternity ClinicExpectations Mothers have poor knowledge about tubectomy contraception and there are still many motherswho have not taken tubectomy contraception. Therefore, it is expected that all mothers who visitHope Maternity Clinic You can understand and use tubectomy contraception.